Geopolitics and Geostrategy - a historical roadmap to a New World Order - Veljanovska Blazhevska, Katerina (National Interest, 2022)
Within the analysis presented in the book “The Grand Chessboard: American Primacy and Its Geostrategic Imperatives”, Zbigniew Brzezinski, the author, diplomat and political scientist, is determining the coordinates of future world developments, and he pays special attention to the analysis of China’s positions [1]. Namely, he analyses that despite all the efforts for an accelerated development, this inhabited country continues to grow its national income by three times by 2020, but it will still be a poor country. Following, it alludes to the fact that the world is entering new global dimensions that are difficult to be realistically predict, as they depend on several existing factors, and above all the level of technological development, economic impact and aspirations for the future alliances In this regard, the future geo-political scene is influenced by numerous opportunities for the creation of new alliances, attempts to build multilateralism, in order to see the real relations of power, which in turn lead to the reorganization of the international relations.